Composition of the avifauna present at the Universidad Nacional Mayor de San Marcos, Lima, Peru - Macedo-Bedoya, Jehoshua (2025)
The main campus of the National University of San Marcos (UNMSM), located in Lima, Peru, has green areas that function as refuges for a significant diversity of birds. The aim of this research was to determine the species composition of the avifauna present on the main campus of the National University of San Marcos, Lima, Peru. Observations were carried out between August 2024 and July 2025, during the morning and afternoon hours. Thirty-three species were recorded, distributed across 10 orders and 18 families, with the Passeriformes order and the Thraupidae family predominating. The most representative trophic guilds were granivores and insectivores equally (27.3%), which is consistent with patterns typically observed in urban environments. Furthermore, the adaptation of Chordeiles acutipennis (Hermann, 1783) to archaeological sites on campus was documented, highlighting the importance of these sites as microhabitats for local fauna. This work highlights that, despite its location in a metropolis, the university campus maintains significant avian diversity, emphasizing the crucial role of urban green areas for conservation.